Pengaruh Gaya Kepemimpinan Demokratis Terhadap Motivasi Kerja Karyawan Sales Bank Rakyat Indonesia Cabang Muara Teweh - Lufina, Lilik (JURNAL ILMU EKONOMI (MANAJEMEN PERUSAHAAN) DAN BISNIS, 2020)
This study aims to determine how much influence the democratic leadership style has on the work motivation of the sales employees of BRI Muara Teweh Branch. The data processing technique used by the author is a simple linear regression analysis used to predict how changes in the value of the dependent variable will increase or decrease the value of the independent variable. The results of data collection are obtained. From the regression model equation, it is known that the Democratic Leadership variable (X) shows a positive regression coefficient value, this indicates a positive direction or a unidirectional relationship between the variable Democratic Leadership Style and Work Motivation for sales employees of BRI Bank Muara Teweh Branch. This means that if the democratic leadership increases, the work motivation of sales employees of BRI Bank Muara Teweh branch will increase, and vice versa if the democratic leadership decreases, the work motivation of sales employees of BRI Bank Muara Teweh branch will decrease. The results of the study concluded that the correlation coefficient (R) shows a close relationship between the independent variable (democratic leadership) and the dependent variable (work motivation), with a correlation value of R is 0.711. While the value of the coefficient of determination or R2 by 0505, which means that 50.5% of working motivation can be explained by the Democratic leadership. For further researchers, it is suggested to look at other leadership style variables.